Étude sur les obstacles à la mise en place d’activités d’engagement civique en milieu scolaire au Québec - Gingras, Marie-Pier; Philippe, Frédérick L.; Poulin, François; Robitaille, Jean (Canadian Journal of Education/Revue canadienne de l’éducation, 2018)
This study surveyed 46 school workers in order to investigate factors that can impede youths’ engagement in civic activities at school in the Province of Quebec. The results confirmed that structural impediments and the lack of information represent hurdles to the development of civic engagement activities. Other barriers related to employees and work conditions emerged. Moreover, school workers’ justification of the system can have an indirect effect on their own civic behaviour, thus potentially diminishing their civic mobilization in school settings. These results suggest courses of action to promote civic activities to youths within school settings.